2007
DOI: 10.3748/wjg.v13.i47.6419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fatty liver disease and its risk factors in the population of South China

Abstract: AIM:To investigate the population-based prevalence of fatty liver disease (FLD) and its risk factors in Guangdong Province, China. METHODS:A cross-sectional survey with multiple-stage stratified cluster and random sampling of inhabitants over 7-year-old was performed in 6 urban and rural areas of Guangdong Province, China. Questionnaires, designed by co-working of epidemiologists and hepatologists, included demographic characteristics, current medication use, medical history and health-relevant behaviors, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 31 publications
10
129
3
3
Order By: Relevance
“…The 40.0% prevalence of ultrasound-diagnosed NAFLD in our study population was higher than the prevalence observed in previous ultrasoundbased cross sectional studies of the general population in Italy [3] (20 %) or Israel [6] (30.5%), as well as in Taiwan [7] (11.5 %), China [9,10] (15.3% and 17.2%), Sri Lanka [8] (32.6%) and Texas [5] (33% in whites, using magnetic resonance spectroscopy). Most likely, this difference can be explained or may have been expected, respectively, based on the higher prevalence of (components of) the metabolic syndrome in patients as compared to randomly selected individuals within the general population.…”
Section: Discussioncontrasting
confidence: 77%
“…The 40.0% prevalence of ultrasound-diagnosed NAFLD in our study population was higher than the prevalence observed in previous ultrasoundbased cross sectional studies of the general population in Italy [3] (20 %) or Israel [6] (30.5%), as well as in Taiwan [7] (11.5 %), China [9,10] (15.3% and 17.2%), Sri Lanka [8] (32.6%) and Texas [5] (33% in whites, using magnetic resonance spectroscopy). Most likely, this difference can be explained or may have been expected, respectively, based on the higher prevalence of (components of) the metabolic syndrome in patients as compared to randomly selected individuals within the general population.…”
Section: Discussioncontrasting
confidence: 77%
“…16,20 Most, though not all, studies have shown that advancing age and male sex affect the risk of NAFLD, independently of coexisting MetS features. [21][22][23][24][25][26] Other studies, although confirming that men are at higher risk of NAFLD, have shown an inverse association between NAFLD and age. [27][28][29][30] Conversely, in women, advancing age, menopausal status and MetS features are all independent predictors of NAFLD.…”
Section: 15mentioning
confidence: 96%
“…As an exam ple, NAFLD prevalence in the populations of Chengdu (southwest China), Shanghai (east China), Guangdong (south China) and central China was 12.5%, 15.0%, 17.0% and 24.5%, respectively [45][46][47] . On the other hand, an ultrasonography study of 7,152 workers in Shanghai published in 2012 suggested that NAFLD prevalence was as high as 38.17% 48 .…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 99%